Consumer Relations through Digital Communication Strategy: A Case Study of After-Sales Service At Pt. Bardi Solusi Otomasi (International Journal of Scientific Research and Management (IJSRM), 2024)
This research was conducted to analyze the digital communication strategy implemented by PT Bardi Solusi Otomasi in providing after-sales services to consumers who have purchased Bardi products. In the initial observation, researchers noticed an increased focus on services delivered to consumers through digital communication in the context of after-sales. The qualitative research method, relying on observation and interviews, was applied to collect data from PT Bardi Solusi Otomasi and consumers who have placed repeat orders. In relation to Computer-Mediated Communication and Customer Relationship Management, the research results indicated that the company could address problems and maintain consumer relations effectively through the Forum Diskusi channel.